Mapping competency profiles of schools of public health: implications for public health workforce education and training in Israel - Neumark, Yehuda; Hannink Attal, Jordan; Shapiro, Naham; MacLeod, Fiona; Harrington, Janas; Barach, Paul; de Nooijer, Jascha; Dopelt, Keren; Duplaga, Mariusz; Leighton, Lore; Levine, Hagai; Mor, Zohar; et al. (Frontiers in Public Health, 2024)
Aim Competency frameworks are essential for analyzing capabilities of Schools of Public Health to adequately prepare public health (PH) professionals to address contemporary challenges. This study maps the competency profiles of PH training programs in Israel using a novel curriculum mapping tool. Methods This study assessed all five Israeli Health Education Institutions (HEIs) offering MPH or Bachelors in Public Health (BPH) degrees across 57 competencies in six domains to determine the extent to which competencies were addressed in the curriculum. The competencies list was based on the Association of Schools of Public Health in the European Region (ASPHER) List of Core Competences for the Public Health Professional, adapted for Israeli HEIs. Results The core curricula in the four MPH programs addressed 45%-84% of all competencies. The BPH program addressed 79% of competencies. In MPH programs, the core curricula addressed most or all competencies in the Methods and the Socioeconomic Determinants of Health domains. Competencies in the domains of Environmental Determinants of Health, Health Policy, Economics & Organization, and Health Promotion and Prevention were less comprehensively addressed in most core curricula. Students' opportunities to broaden their exposure to competencies outside the core curricula were context dependent. Discussion The curriculum competencies mapping tool that was developed served to assess both strengths and shortcomings in PH education in Israel. The findings demonstrate a highly variable array of PH curriculum models in Israeli HEIs, as well as overall shortcomings in the Environmental, Health Policy Economics and Organization, and Health Promotion and Prevention domains. This analysis has already led to reassessment of the curriculum, and will continue to guide the next steps to increase the harmonization of PH training curricula and to better meet PH challenges in Israel.